Exaggerated and prolonged thyrotrophin releasing hormone (TRH) test responses in tertiary hypothyroidism. - Mills, G H (1991)
A 60 year old man with panhypopituitarism due to a large meningioma and prolonged and exaggerated thyroid stimulating hormone (TSH) responses is described. Initial investigations showed a subnormal urinary free cortisol concentration, a low serum cortisol taken at 0900 hours, and a low free T4 concentration. The TSH was towards the upper end of the normal range. Subsequently pituitary function tests showed subnormal production of luteinising hormone in response to luteinising hormone releasing hormone (LHRH) and a short synacthen test with a low 30 minute cortisol value. Long synacthen testing showed a normal response at four days, confirming that the abnormalities were due to a pituitary or hypothalamic cause. A computed tomogram showed a large meningioma compressing the hypothalamus, pituitary, and temporal lobe. TRH testing showed a prolonged and exaggerated response, consistent with tertiary hypothyroidism.